Rethinking school bullying : dominance, identity and school culture - Jacobson, Ronald B. (Routledge research in education ;, 2013)
"This book takes a new angle on a much-studied phenomenon, focusing on the role of domination and identity construction, understanding and self-knowledge, moral transformation and the social community, systems of training and hierarchy used by schooling, and the role they play in bullying. Exploring typical narratives of value within schooling (i.e., who counts and who doesn't?), the volume shows how bullying might make sense to a student as a pathway of identity construction within such stories (discourses and practices taken up by schools). It suggests how we can "tell a new story" and create a new culture which might undermine, or close off, the allure of bullying as a "need-meeting" avenue for students within schools"--